2010
DOI: 10.1148/radiol.10092021
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MR Imaging: Pretreatment Prediction of Response to Neoadjuvant Chemotherapy in Patients with Breast Cancer

Abstract: Patients with breast cancer and a low pretreatment ADC tended to respond better to chemotherapy. Prediction of response to neoadjuvant chemotherapy with DW MR imaging might help physicians individualize treatments and avoid ineffective chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
171
3
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(197 citation statements)
references
References 33 publications
20
171
3
3
Order By: Relevance
“…However, for prediction of pathologic response, the ADC parameters did not stand out as important (mean error rate 0.5). Similar results have been shown recently (34), although others report that tumors with low ADC values before NAC respond better to chemotherapy (35). The baseline ADC values in the present study were in good agreement with other results in malignant breast cancer (14).…”
Section: Discussionsupporting
confidence: 93%
“…However, for prediction of pathologic response, the ADC parameters did not stand out as important (mean error rate 0.5). Similar results have been shown recently (34), although others report that tumors with low ADC values before NAC respond better to chemotherapy (35). The baseline ADC values in the present study were in good agreement with other results in malignant breast cancer (14).…”
Section: Discussionsupporting
confidence: 93%
“…Intact cell membranes in viable tumor tissues exhibit restricted water diffusion, thus presenting a correspondingly low ADC, while disrupted cellular integrity in necrotic tissues results in increased water diffusion, thus exhibiting a corresponding increase in ADC value (34). The finding that necrotic areas in tumors with high ADC pre values are likely to reduce the delivery of CCRT agents to the tumor is likely due to poor perfusion coupled by a hypoxic environment and reduced metabolism, thus causing the area to be less sensitive to CCRT and to exhibit a smaller regression rate (33). However, when CCRT was initiated gradually, tumor necrosis and apoptosis followed by reduced tumor cellularity and expanded extracellular space resulted in the disintegration of intact cell membranes and more unrestricted movement of water molecules, thus causing an increase in ADC mid and ADC post value together with a correspondingly proportional reduction in tumor size (28,35) .…”
Section: Discussionmentioning
confidence: 99%
“…The most important conclusion of the current study is that the ADC values of lymph nodes with metastasis was apparently lower compared to those of benign or normal lymph nodes, indicating that DWI might be an useful method in the characterization and diagnosis of malignant LNM in BC patients by means of measuring the ADC values. DWI has been widely supported to provide quantitative and qualitative functional information from water molecules diffusion, which primarily reflects the degree of tissues cellularity, and meanwhile, several evidence has showed that DWI has been evaluated in various cancers including cervical cancer and BC (Hamstra et al, 2007;Park et al, 2010;Downey et al, 2013). The technology of DWI adopts DW gradient pulses to produce signals which are susceptible to the localized diffusivity of water molecules and thus can indirectly measure cell density, microstructure, cell organization or LNM (Padhani et al, 2009).…”
Section: Discussionmentioning
confidence: 99%